2023
DOI: 10.1101/2023.05.19.541423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centralin vivomechanisms by whichC. difficile’sproline reductase drives efficient metabolism, growth, and toxin production

Abstract: Clostridioides difficile (CD) is a sporulating and toxin-producing nosocomial pathogen that opportunistically infects the gut, particularly in patients with depleted microbiota after antibiotic exposure. Metabolically, CD rapidly generates energy and substrates for growth from Stickland fermentations of amino acids, with proline being a preferred reductive substrate. To investigate the in vivo effects of reductive proline metabolism on C. difficile virulence in an enriched gut nutrient environment, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…8 ). In line with previous studies ( 5 , 29 , 30 ), C. difficile WT displayed proline-dependent growth, leading to higher cell density at higher proline levels. In contrast, the growth of the Δ prdH -mutant was found to not respond to proline.…”
Section: Resultssupporting
confidence: 92%
“…8 ). In line with previous studies ( 5 , 29 , 30 ), C. difficile WT displayed proline-dependent growth, leading to higher cell density at higher proline levels. In contrast, the growth of the Δ prdH -mutant was found to not respond to proline.…”
Section: Resultssupporting
confidence: 92%
“…5-aminovalerate and proline were highly correlated with both tcdA and tcdB , in agreement with previous results based on correlations between time points [13]. This also corroborates work that has suggested that the Stickland reaction is necessary for robust C. difficile growth [42, 33, 43, 44]. Hydroxyphenyl propionate, guanosine, and sedoheptulose were also partially correlated with tcdA and tcdB .…”
Section: Resultssupporting
confidence: 91%
“…These results highlight the need to further investigate biochemical mechanisms underpinning these relationships. Both proline and 5-aminovalerate are involved in the Stickland reaction which provides energy to C. difficile [42, 33, 43, 44]. Through this reaction, C. difficile proline reductase reduces proline to 5-aminovalerate by using an electron donated to NADH by an amino acid (typically branched chain amino acids) from the oxidative branch of the Stick-land reaction [52].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations